Role of Low Molecular Weight Heparin (LMWH) in the Treatment of Recurrent Missed Abortion - Begum, Mosammat Rashida; Ehsan, Mariya; Ehsan, Nazia; Amin, Iftekhar; Sharmin, Farhana; Chowdhury, Ashik Ahmed; Khan, Farzana; Santa, Mosammat Shahina Begum (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective (s): The aim of this study was to explore the outcome of treatment of low molecular weight heparin (LMWH) in recurrent missed abortion cases. Method: This prospective observational study was done between January 2005 and July 2014 in Infertility Care and Research Center, Dhaka, Bangladesh. Two hundred and ten (210) patients who were able to give clear history of missed abortion, who had no endocrine and hypertensive disorders and who conceived spontaneously or after fertility treatment were the target population for this study. After positive pregnancy test all patients started taking oral progesterone (Dydrogesterone 10 mg bd), folic acid and aspirin 75 mg daily. Patients were advised to come for ultrasonography at 6 weeks of pregnancy. After confirming intrauterine viable pregnancy by ultrasonography we started injection enoxaparin (LMWH) 40 mg sc daily to all patients and continued till 34 completed weeks. The primary end point was the live birth rate and secondary end points were the side effects, late pregnancy complications and neonatal outcome in the study population. Results: One hundred and nine (52.39%) patients had antiphospholipid syndrome. Among them antiphospholipid subgroup antibody found in 40.37% cases, ACLA found in 27.52% cases, LA found in 18.34% cases and both ACLA and LA found in 13.77% cases. Antinuclear antibody was positive in 10% cases. No abnormality was identified in 38.09% cases. Pregnancy continued successfully in 96.66% cases. There were no maternal and foetal complications. Except failed cases there was no need to discontinue the treatment. Conclusion: This observational study dealt only with recurrent missed abortion and found satisfactory outcome with low dose heparin therapy. Large, well-designed randomized trials are needed to establish the heparin therapy in recurrent missed abortion. Bangladesh J Obstet Gynaecol, 2014; Vol. 29(2) : 94-101